INS/CNS/GNSS Integrated Navigation Technology - Quan, W (Springer, 2015)
This book not only introduces the principles of INS, CNS and GNSS, the related filters and semi-physical simulation, but also systematically discusses the key technologies needed for integrated navigations of INS/GNSS, INS/CNS, and INS/CNS/GNSS, respectively. INS/CNS/GNSS integrated navigation technology has established itself as an effective tool for precise positioning navigation, which can make full use of the complementary characteristics of different navigation sub-systems and greatly improve the accuracy and reliability of the integrated navigation system. The book offers a valuable reference guide for graduate students, engineers and researchers in the fields of navigation and its control.